Hair we grow again: Upward mobility, career compromise, and natural hair bias in the workplace. Issue 3 (16th August 2022) - Summers, LaTonya M.; Davis, Tonya; Kosovac, Bilal
Abstract: Natural hair bias, the targeting of people based on their hair or hairstyle, is an emerging but recurring barrier Black women face in the workplace. The aim of this qualitative study was to investigate whether early‐career Black women perceived that their ability to advance occupationally was compromised by wearing natural hair. Semi‐structured interviews were conducted with nine Black women with less than 2 years of work experience in various professions. Using interpretative phenomenological analysis (IPA), the researchers extracted five main themes: appearance and professionalism, double standards, natural hair journey, identity, and invisible rules of engagement at work.